Defense Against Biological Weapons (Biodefense) - Georgiev, Vassil St. (National Institute of Allergy and Infectious Diseases, NIH, 2009)
Biological warfare (germ warfare) is defined as the use of any disease-causing organism or toxin(s) found in nature as weapons of war with the intent to destroy an adversary. Though rare, the use of biological weapons has occurred throughout the centuries.